Design and Development of a Website for Improving Sales Efficiency of Horticultural Ornamental Plant SMEs in Lubuk Minturun - Hayati Rahmatika; Lativa Mursyida; Denny Kurniadi; Geovanne Farell (Sagamedia Teknologi Nusantara, 2023)
This research aims to design and develop a dedicated website for managing Small and Medium-sized Enterprises (SMEs) specializing in ornamental plants in the Agrotourism area of Lubuk Minturun. The website focuses on the needs of SMEs and ornamental plant buyers. The development method employed is the MVC (Model, View, Controller) architecture using the Waterfall approach to provide an organized development structure. The website offers services such as SMEs event schedules and facilities for buying and selling ornamental plant products. The successful provision of these services is expected to promote and support SMEs in ornamental plants in the area. The utilization of technologies such as the PHP programming language, Yii Framework, and MySQL database provides a solid technological foundation, ensuring the efficiency and scalability of the website. In conclusion, the design of this website not only establishes a platform for SMEs and brings positive benefits to the business development and promotion of ornamental plants in the Agrotourism area of Lubuk Minturun. With the proper technological support, it is anticipated that this website will enhance the competitiveness of SMEs and add value to stakeholders in the horticultural ornamental plant sector.